Prediction and experimental characterization of the molecular architecture of FRP and ATRP synthesized polyacrylate networks - Gonçalves, Miguel A.D. (2010)
This work reports experimental and modeling studies concerning the conventional (FRP) and atom transfer radical polymerization (ATRP) of acrylate/diacrylate monomers. In the framework of a recently developed general approach, kinetic models including crosslinking reactions and branching by chain transfer to polymer are discussed for FRP and ATRP polymerization systems. Besides molecular weight distribution (MWD), fairly good predictions of the z-average radius of gyration could be obtained for these non-linear polymers. A set of experiments was performed at 1 L scale in a batch reactor using n-butyl acrylate (BA) or methyl acrylate (MA) as monovinyl monomers and 1,6-Hexanediol diacrylate (HDDA) or bisphenol A ethoxylate diacrylate (BEDA) as crosslinkers. In FRP experiments, AIBN was used as initiator and ATRP polymerizations were initiated by ethyl 2-bromopropionate (EBrP) and mediated by CuBr using PMDETA (N,N,N,N,N-pentamethyldiethylenetriamine) as ligant. Polymerizations were carried out in solution at 60 °C with different dilutions using toluene and DMF as solvents. Products formed at different polymerization times were analyzed by SEC/RI/MALLS yielding average MW, MWD, z-average radius of gyration and monomer conversion. Important differences in the molecular architecture of the synthesized FRP and ATRP highly branched polyacrylates have been identified. Comparisons of experimental results with predictions have put into evidence the important effect of intramolecular cyclizations at all dilutions, even with ATRP polymerizations.